Clinical researchProlonged postoperative recovery following surgical repair for congenital heart disease in young children - Ídiz, Mustafa; Konuralp, Cüneyt; Çine, Nihat; Aydemir, Numan A.; Enç, Yavuz; Yapici, Nihan; Aykaç, Zuhal; Çiçek, Sertaç; Bilal, Mehmet S. (Archives of Medical Science, 2008)
Introduction: We aimed to draw a profile of young children undergoing surgical repair for congenital heart disease (CHD), who have prolonged postoperative recovery, and compared this profile with the profile of a shorter postoperative recovery time group. Material and methods: Data of 147 consecutive patients aged younger than 36 months undergoing cardiac surgery for CHD were reviewed, and they were allocated to two groups based on the duration of intensive care unit (ICU) stay equal to or less than 7 days (group I, n=114), and more than 7 days (group II, n=33). Results: The patients in group II were significantly younger (10.2±3.9 months vs. 19.9±5.8 months; P<0.001). Aortic cross-clamp times were 39.1±3.6 min in group I, and 50.4±8.7 min in group II (P<0.05). Extubation failures (more than 48 hours) occurred in 3 cases in group I, compared to 29 patients in group II (P<0.0001). A total of 28 patients (7 in group I, and 21 in group II) developed pulmonary complications. These patients contributed to the majority of total ventilator days (69%) as well as ICU stay (58%). Fourteen percent of patients underwent staged operations in group I, compared to 48.5% in group II (P<0.002). Conclusions: Pulmonary complications seem to be one of the most important causes of delayed recovery following cardiac surgery in young children. We suggest that extubation time is a crucial factor for development of pulmonary problems. This factor might be more important for infants who undergo staged operations.